Gene expression regulatory networks in Trypanosoma brucei: insights into the role of the mRNA-binding proteome - Lueong, Smiths; Mercé, Clémentine; Fischer, Bernd; Hoheisel, Jörg D.; Erben, Esteban D. (Molecular microbiology, 2016)
Control of gene expression at the post-transcriptional level is essential in all organisms, and RNA-binding proteins play critical roles from mRNA synthesis to decay. To fully understand this process, it is necessary to identify the complete set of RNA-binding proteins and the functional consequences of the protein-mRNA interactions. Here, we provide an overview of the proteins that bind to mRNAs and their functions in the pathogenic bloodstream form of Trypanosoma brucei. We describe the production of a small collection of open-reading frames encoding proteins potentially involved in mRNA metabolism. With this ORFeome collection, we used tethering to screen for proteins that play a role in post-transcriptional control. A yeast two-hybrid screen showed that several of the discovered repressors interact with components of the CAF1/NOT1 deadenylation complex. To identify the RNA-binding proteins, we obtained the mRNA-bound proteome. We identified 155 high-confidence candidates, including many not previously annotated as RNA-binding proteins. Twenty seven of these proteins affected reporter expression in the tethering screen. Our study provides novel insights into the potential trypanosome mRNPs composition, architecture and function.
Gesehen am 19.05.2020